Violence prevention climate in general adult inpatient mental health units : validation study of the VPC‐14 - Dickens, Geoffrey L. (R (2020)
Ward social climate is an important contributor to patient outcomes in inpatient mental health services. Best understood as the general ‘vibe’ or ‘atmosphere’ on the unit, social climate has been subject to a significant research aimed at its quantification. One aspect of social climate, the violence prevention climate, describes the extent to which the ward is perceived as safe and protective against the occurrence of aggression by both the patients and the staff. The violence prevention climate scale (VPC‐14), developed in a UK forensic setting, was used in this study in a test of its validity in an Australian general mental health setting. The VPC‐14 was administered across eleven wards of one metropolitan Local Health District in Sydney, NSW. N = 213 valid responses from nursing staff and patients were returned (response rates 23.4 and 24.3%, respectively). The VPC‐14 demonstrated good internal reliability, and convergent validity was evidenced through moderate correlations with the WAS's anger and aggression subscale and the GMI total score. Concurrent validity was demonstrated by expected staff–patient differences in VPC‐14 rating and by correlations between incidents of conflict and containment on wards and the VPC‐14 ratings of staff and patients from those wards. Rasch analysis suggested that future tool development should focus on identifying ways to discriminate between ratings at the high end of the scale. The VPC‐14 supplies valid and useful information about the violence prevention climate in general adult mental health wards